Risk Detection in Digital Information Management: A Records Management Perspective - Harry Bawono (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2020)
The Presidential Regulation on e-Government in 2018 became the starting point for accelerating e-Government implementation in Indonesia. This moment prompted government agencies to compete in digitizing their organizations to apply the regulation. Digital information as the output of this massive digitalization will be abundant and must be managed properly which is certainly vulnerable to threats. Such threats can compromise the authenticity of records and make them untrustworthy. An adequate risk detection framework that fits the context of the digital environment is needed to minimize these incidents. This framework contains a records management perspective that has undergone a paradigmatic shift. This framework adopts the view that records management is an integral part of digital information management. The study used a qualitative method and found that from the perspective of records management, the risk detection framework in digital information management sheds light on aspects of context (external and internal), systems, and processes. However, its smooth implementation in the digital environment, especially in Indonesia, is determined by the extent to which paradigmatic reforms in records management have taken place.